2010
DOI: 10.1021/jp9082322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AlF3Coating on Thermal Behavior of Chemically Delithiated Li0.35[Ni1/3Co1/3Mn1/3]O2

Abstract: The thermal behavior of chemically delithiated Li0.35[Ni1/3Co1/3Mn1/3]O2 and the AlF3-coated material was studied in the temperature range from room temperature to 600 °C. Thermogravimetric analysis results showed that the uncoated and the AlF3-coated Li0.35[Ni1/3Co1/3Mn1/3]O2 powders experienced distinct weight loss with increasing temperature, of which the weight loss was ascribed to oxygen release from the active materials. The released oxygen amount was less for the AlF3-coated Li0.35[Ni1/3Co1/3Mn1/3]O2 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 36 publications
(55 reference statements)
8
59
0
1
Order By: Relevance
“…The thermal stability decreases and the temperature of the main exothermic reaction is shifted to~236 • C. The ratio between the exothermic peaks changes and the heat release increases more than twofold. Such differences may be related to the surface and bulk changes of the cathode material upon cycling, and the results obtained correlate well with previous reports [58][59][60][61]. To summarize, the surface modification by AlF 3 coating of these Li-and Mn-rich cathode materials improves their thermal stability in pristine and delithiated states compared to the uncoated electrodes.…”
Section: Modifications Of XLIsupporting
confidence: 89%
“…The thermal stability decreases and the temperature of the main exothermic reaction is shifted to~236 • C. The ratio between the exothermic peaks changes and the heat release increases more than twofold. Such differences may be related to the surface and bulk changes of the cathode material upon cycling, and the results obtained correlate well with previous reports [58][59][60][61]. To summarize, the surface modification by AlF 3 coating of these Li-and Mn-rich cathode materials improves their thermal stability in pristine and delithiated states compared to the uncoated electrodes.…”
Section: Modifications Of XLIsupporting
confidence: 89%
“…In other words, the NMC structure is thermodynamically unstable at high degrees of delithiation, and only retains its oxygen and its layered bulk structure due to the kinetically hindered oxygen diffusion. This hypothesis is supported by the literature, where it is reported that layered NMC 21,25,27,70,71 and NCA 22,25,26,70 structures in the charged state (low lithium content) are not stable at high temperatures (> 170…”
Section: Discussionsupporting
confidence: 74%
“…Due to the large amount of Mn in the shell, the oxidation state of Mn is close to tetravalent and the oxidation state of Ni is close to Ni 2 + , slightly higher than 2 + based on XPS data (Supporting Information, Figure S1) which is similar to our previous results of Li [ [19] We considered two possibilities for cation mixing: i) Li layer occupation of Ni 2 + from the transition metal layer, and ii) site exchange of Li + and Ni 2 + . The latter case always resulted in a smaller intensity of the difference between the observed and calculated patterns and better reliability factors (R wp and R p values), as shown in Table 2 and Table 3.…”
Section: Thermal Lithiation Of Cgcs Hydroxide Composed Of Nanoparticlsupporting
confidence: 89%